2013
DOI: 10.1016/j.jenvrad.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of lightweight gamma spectrometry systems in urban environments

Abstract: Urban areas present highly complex radiation environments; with small scale features resulting from different construction materials, topographic effects and potential anthropogenic inputs from past industrial activity or other sources. Mapping of the radiation fields in urban areas allows a detailed assessment of exposure pathways for the people who live and work there, as well as locating discrete sources of activity that may warrant removal to mitigate dose to the general public. These areas also present ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Measurements with and without human operators in radiation fields dominated by 137 Cs and 134 Cs were conducted at a ground sampled calibration site at Fukushima University (Sanderson et al 2013). These measurements are shown in Figure 5, and give reductions in the full energy intensities for 134 Cs and 137 Cs of 25-30%, which are consistent with the results of the numerical model developed in this study, and with the experimental values obtained from the substitute experimental geometry.…”
Section: Results Of the Field Validationsupporting
confidence: 81%
See 1 more Smart Citation
“…Measurements with and without human operators in radiation fields dominated by 137 Cs and 134 Cs were conducted at a ground sampled calibration site at Fukushima University (Sanderson et al 2013). These measurements are shown in Figure 5, and give reductions in the full energy intensities for 134 Cs and 137 Cs of 25-30%, which are consistent with the results of the numerical model developed in this study, and with the experimental values obtained from the substitute experimental geometry.…”
Section: Results Of the Field Validationsupporting
confidence: 81%
“…These measurements are shown in Figure 5, and give reductions in the full energy intensities for 134 Cs and 137 Cs of 25-30%, which are consistent with the results of the numerical model developed in this study, and with the experimental values obtained from the substitute experimental geometry. Comparisons between measurements with the backpack system and data from soil samples at the ECCOMAGS calibration sites (Sanderson et al 2004) close to the Solway Firth in Scotland (Cresswell et al 2013) have also shown reductions of 20% to 40% between the field measurements and samples. The magnitude of the observed reductions is compatible with the estimate from the model presented here.…”
Section: Results Of the Field Validationmentioning
confidence: 97%
“…Typically in areas of lower radioactivity rock, longer sample times are needed for suitably accurate results [22]. An alternative approach used by some surveys is to monitor continuously then integrate the count times in intervals, e.g., every 5-10 s [50]. Rock and soil samples can also be collected during these in-situ surveys, to compare with the in-situ gamma results or to conduct more general rock mineral analysis [32,33,44,51] and be able to quantify near surface geometrical effects [52].…”
Section: Instrumentationmentioning
confidence: 99%
“…Indeed some designs have been specifically mounted on backpacks and readings taken at automatic intervals [32,50]. Such portable spectrometers have precisions of approximately 0.1%-0.14% K, 0.6-0.8 ppm eU, and 0.6-1.5 ppm eTh [42,53].…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation